Intending the Spirits: Experiencing Vodu Through the “Fetish” in Togo - Vannier, Christian N. (Material religion, 2020)
Early encounters with Africa initiated a European fascination with the “fetish.” Though this term has been extensively problematized, anthropologists have kept the term, reading fetishes as cultural texts and searching to untangle the material assemblages and deep symbols that comprise them. This article contributes to our knowledge of fetishes by applying a practitioner-centric approach to their use and meaning in the matrices of Vodu. First, I elucidate meanings of these spiritual embodiments using ethnography of prayer and sacrifice in Gorovodu as practiced by ethnic Ewe and Mina communities in southern Togo. I then deploy the language of phenomenological anthropology to argue that fetishes bring intentionality into being and focus. Their filled presence directs consciousness towards the spirits and allows practitioners to sensuously experience spirituality and spiritual being. Rituals surrounding material fetishes are a means of intending reciprocal relationships with the divine into perceptual consciousness, and it is through these relationships that life and success are made possible.